Orbital marginal cell lymphoma and mantle cell lymphoma subclone in patient with monoclonal gammopathy of unknown significance. (4th May 2021) - Hirji, Sitara H.; Maeng, Michelle M.; Tooley, Andrea A.; Soderquist, Craig; Annunziata, Joseph; Kazim, Michael
ABSTRACT: Indolent lymphomas have the potential to transform into more aggressive phenotypes. This phenomenon is best exemplified by the transformation of chronic lymphocytic leukemia/small lymphocytic lymphoma into diffuse large B-cell lymphoma. However, it is less common to find multiple small cell lymphomas in the orbit, particularly mantle cell lymphoma. We present a case of an extranodal marginal zone lymphoma arising in the orbit that acquired a subclonal t(11;14) (q13;32) CCND1-IGH translocation, giving rise to a subclone of mantle cell lymphoma. The management of this tumor was targeted towards the more aggressive mantle cell subclone. The tumor exhibited an incomplete response to rituximab alone. To the best of the authors' knowledge, this represents the first such case to be described irrespective of site of origin.